The development and evaluation of a solar-powered refrigerator using activated carbon/ methanol pair (2009)
A solar-powered adsorption refrigerator using activated carbon/methanol pair was designed and fabricated. The refrigerator has three major components: collector-condenser, and evaporator. A 3 mm thick flat glass was used as flat plate collector. The condenser was made of spirally coiled copper tube immersed in pool of stagnant water contained in a reinforced sancrete tank. The .evaporator was fabricated from standard 15.6 mm diameter copper tubing. The activated carbon used as adsorbent was manufactured locally from shells of a palm kernel. The maximum temperature of 108°C attained in the solar collector was adequate for methanol generation, while maximum received insolation of 1000 kW/m2 was sufficient for methanol desorption. The solar coefficient of performance (COP) of the refrigerator ranged from 0.0339 to 0.0345 compared to 0.03 to 0.055 recorded in the literature. The study shows that a solar powered adsorption refrigerator will operate In Nigeria's tropical climate with satisfactory coefficient of performance.